Adenocarcinoma not otherwise specified (NOS) arising in the sublingual gland: Rare case report and follow-up. (March 2022) - Silva, Luan César; Faustino, Isabel Schausltz Pereira; Cantadori, Gabriela Rossi; Santos-Silva, Alan Roger; Vargas, Pablo Agustin; Lopes, Márcio Ajudarte
Abstract: Background: Adenocarcinoma not otherwise specified (AdCaNOS) is a rare malignant salivary gland tumor that occurs with higher frequency in the parotid gland of male patients. In this study, we described a second case of AdCaNOS arising in the sublingual gland, in a female patient with 39 years of age, highlighting the clinical, radiographic, microscopic, treatment features and follow-up. Case report: A 39-year-old female patient presented a fibroelastic nodule with a yellowish coloration, in the left region of the floor of mouth, measuring about 4.0 cm in its largest diameter. An incisional biopsy was performed and the main microscopic features revealed an infiltrative lesion with glandular differentiation organized in cystic spaces, where neoplastic cells secreting eosinophilic material were observed. The tumor showed immunopositivity for pancytokeratin (AE1/AE3), keratins 7 (CK7) and 14 (CK14), and negativity for p63. The proliferation level measured by Ki-67 marker was considered higher. The patient underwent radical surgical resection, but unfortunately, she developed local recurrence, lymph node mestastasis and died 1.5 year after diagnosis. Conclusion: Although rare in the sublingual gland, particularly at this age, AdCaNOS can occur and early diagnosis and early treatment are essential for a better prognosis and survival rates of the patients.